980 Technological Innovations in The Management of Pressure Ulcers: A Systematic Review and Discussion. (12th October 2021) - Srivastava, A; Khanal, P; Zargaran, D; Zoller, F; Zargaran, A; Mosahebi, A
Abstract: Aim: Pressure ulcers (PUs) affect over 700, 000 patients per annum and are associated with an up to fourfold increase in mortality rate in older populations with complex pathologies. NICE guidelines for PU management involve a combination of low-grade technological interventions, including dressings and foam mattresses, while technology-centric therapies are not offered. The aim of this systematic review is to evaluate the effectiveness of any novel and high-grade technological PU interventions. Method: The PubMed, Embase (via Ovid), Web of Science and CINAHL databases were electronically searched using free-text and MeSH search strings. Results evaluating the type of technological intervention, outcome measures and wound healing rates, duration of hospital stay, requirement for surgical debridement, infection and mortality rates were methodically assessed. Results: An initial search identified 900 articles. Using the PRISMA guidance, 25 studies were included, encompassing 845 patients. 28 novel modalities of high-grade innovations were identified, with distinguished technologies including smart wireless bandages and 3D-printed wound repair scaffolds. Overall, 92.8% of devices demonstrated an improvement in wound healing (P < 0.05). A novel framework was created from the different innovations identified to approach adopting innovation in PU management. Conclusions: The majority of high-technology innovations identified in this systematic review significantly improve PU healing, thus offering an additional pathway to standard care. Given the annual cost of PUs (£531 million), it is vital innovative technologies are considered as the NHS transitions into a digital age. Therefore, further studies are essential and recommended to evaluate the potential benefit of the promising, innovative technologies identified.